The dose–response association of urinary metals with altered pulmonary function and risks of restrictive and obstructive lung diseases: a population-based study in China. Issue 5 (21st May 2015) - Feng, Wei; Huang, Xiji; Zhang, Ce; Liu, Chuanyao; Cui, Xiuqing; Zhou, Yun; Sun, Huizhen; Qiu, Gaokun; Guo, Huan; He, Meian; Zhang, Xiaomin; Yuan, Jing; et al.
Abstract : Objective: Reduced pulmonary function is an important predictor of environment-related pulmonary diseases; however, evidence of an association between exposures to various metals from all possible routes and altered pulmonary function is limited. We aimed to investigate the association of various metals in urine with pulmonary function, restrictive lung disease (RLD) and obstructive lung disease (OLD) risks in the general Chinese population. Design: A cross-sectional investigation in the Wuhan cohort population. Setting: A heavily polluted Chinese city. Participants: A total of 2460 community-living Chinese adults from the Wuhan cohort were included in our analysis. Main outcome measures: Spirometric parameters (FVC, forced vital capacity; FEV1, forced expiratory volumes in 1 s; FEV1 /FVC ratio), RLD and OLD. Results: The dose–response associations of pulmonary function, and RLD and OLD, with 23 urinary metals were assessed using regression analysis after adjusting for potential confounders. The false discovery rate (FDR) method was used to correct for multiple hypothesis tests. Our results indicated that there were positive dose–response associations of urinary iron with FEV1 and FEV1 /FVC ratio, vanadium with FEV1, and copper and selenium with FEV1 /FVC ratio, while a negative dose–response association was observed between urinary lead and FEV1 /FVC ratio (all p<0.05). After additional adjusting for multiple comparisons, only iron was dose dependently related to FEV1 /FVC ratio (FDR adjusted p<0.05). The dose–response association of iron and lead, with decreased and increased chronic obstructive pulmonary disease risk, respectively, was also observed (both p<0.05). Additionally, we found significant association of urinary zinc with RLD and interaction effects of smoking status with lead on FEV1 /FVC, and with cadmium on FVC and FEV1 . Conclusions: These results suggest that multiple urinary metals are associated with altered pulmonary function, and RLD and OLD prevalences.